Impact of the COVID-19 crisis on heavy work investment in Romania - Alina Simona Tecău; Cristinel Petrișor Constantin; Radu Constantin Lixăndroiu; Ioana Bianca Chițu; Gabriel Brătucu (Amfiteatru Economic Journal, 2020)
This paper analyzes aspects specific to the influence of the COVID-19 pandemic on the working population in Romania, from the perspective of heavy work investment. Issues related to workload, overwork, work engagement, workaholism and performance in work were considered. A survey based research was conducted using several scales widely tested in studies on heavy work investment with the data being processed in SPSS. The results of the research reveal a negative impact on the components of heavy work investment (time and effort). For all measured aspects, there were decreases in work investment during the pandemic, with negative effects on respondents' attitudes towards personal work performance. Based on the research results, the main proposal for the business environment is to stimulate employees for achieving a higher level of work engagement which can lead to increased work performance. This can also be achieved by adopting policies to reduce overtime.
Keywords: J22; I13; R11; C83; M31; 330; Heavy Work Investment; work addiction (workaholism); work engagement; excessive working time; COVID-19; dashboard online; work performance